Adapting Mobility Infrastructure to the Needs of a Liveable City: The Case of Beirut Street Markets - Askar, Youssef; Abdel-Ghani, Taher (Alanya Üniversitesi, 2024)
Beirut’s policies in the last decade or more contributed to the creation of a highly car-dependent city with almost 2 million vehicles dominating the streets and causing high traffic congestion. Yet, Beirut’s informal street markets carry the potential for the enhancement of a liveable sustainable city, which previous studies have overlooked. To approach this problem, urban planners need to re-think and restructure the existing street network in Beirut to decrease the distances between the suburbs and the centre of the city. The aim of this research is to formulate a rational system that assigns markets and pedestrian areas to certain streets where cars can have no or limited access. This system adopts a parametric tool based on fuzzy logic which analyzes the current street network and filters out streets that fulfil certain criteria such as parking availability and proximity to public transportation, hence decreasing centrality in the city. This method is applied to both fixed and temporary food markets that are characterized by highly dynamic pedestrian movement. The final results show a series of maps of Beirut with different scenarios identifying streets that fulfil the defined criteria as potential street markets, which can be the blueprint for further analysis of street and transportation planning creating more liveable and sustainable places.